The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1113/ep087198
|View full text |Cite
|
Sign up to set email alerts
|

Two months sodium nitrate supplementation alleviates testicular injury in streptozotocin‐induced diabetic male rats

Abstract: Inorganic nitrate supplementation is a possible therapeutic agent in diabetes. The aim of this study was to evaluate the effect of nitrate on the reproductive system in streptozotocin-induced diabetic male rats. Fifty male Wistar rats were allocated randomly to five groups: control (C), control plus nitrate (CN), diabetic (D), diabetic plus insulin (DI) and diabetic plus nitrate (DN). Sodium nitrate was administered for 2 months in the drinking water (100 mg l ) of the CN and DN groups. Insulin was injected at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 68 publications
(138 reference statements)
0
13
0
Order By: Relevance
“…Overall, the final body weights were significantly lower in the NO 3 supplemented groups compared to controls (WMD= -16.8 g, 95 % CI= -27.38, -6.24; P =0.002) (Figure 2 (Fig. 2) ; References in Figure 2: Ashmore et al, 2015[ 2 ]; El-Wakf et al, 2009[ 6 ], 2015[ 7 ]; Gheibi et al, 2018[ 10 ]; Hezel et al, 2016[ 13 ]; Khalifi et al, 2015[ 21 ]; Khorasani et al, 2019[ 22 ]; Norouzirad et al, 2019[ 31 ]; Oghbaei et al, 2018[ 32 ]; Roberts et al, 2015[ 35 ]; Zaki et al, 2004[ 40 ]); after exclusion of 10 experiments within the arms corresponding to high doses of NO 3 (620 and 401 mg L -1 d -1 ), overall mean differences in body weights between the groups decreased by approximately 37 % but remained statistically significant (WMD= -10.1 gr, 95 % CI= -19.0, -1.19, P =0.026).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the final body weights were significantly lower in the NO 3 supplemented groups compared to controls (WMD= -16.8 g, 95 % CI= -27.38, -6.24; P =0.002) (Figure 2 (Fig. 2) ; References in Figure 2: Ashmore et al, 2015[ 2 ]; El-Wakf et al, 2009[ 6 ], 2015[ 7 ]; Gheibi et al, 2018[ 10 ]; Hezel et al, 2016[ 13 ]; Khalifi et al, 2015[ 21 ]; Khorasani et al, 2019[ 22 ]; Norouzirad et al, 2019[ 31 ]; Oghbaei et al, 2018[ 32 ]; Roberts et al, 2015[ 35 ]; Zaki et al, 2004[ 40 ]); after exclusion of 10 experiments within the arms corresponding to high doses of NO 3 (620 and 401 mg L -1 d -1 ), overall mean differences in body weights between the groups decreased by approximately 37 % but remained statistically significant (WMD= -10.1 gr, 95 % CI= -19.0, -1.19, P =0.026).…”
Section: Resultsmentioning
confidence: 99%
“…Limited animal studies have investigated the anti-obesity effects of inorganic NO 3 as a primary hypothesis (Roberts et al, 2015[ 35 ]), while the majority of the available experiments have only reported data on body weight in NO 3 -treated animals as a secondary crude observation without any significant interpretations. This issue remains even more uncertain since inconsistent results including, higher (Hezel et al, 2016[ 13 ]; Oghbaei et al, 2018[ 32 ]), lower (Zaki et al, 2004[ 40 ]; El-Wakf et al, 2009[ 6 ]; Gheibi et al, 2018[ 10 ]; Khorasani et al, 2019[ 22 ]) or equal (Ashmore et al, 2015[ 2 ]; Khalifi et al, 2015[ 21 ]; Roberts et al, 2015[ 35 ]) weight gain have been reported in control and NO 3 -treated rats.…”
Section: Introductionmentioning
confidence: 99%
“…For example 4, thus sections 4, 17, 30, 43, … were selected for stereological analysis. Finally, ten 5-µm sections per mice were analysed for histological study and 20-25 sections were analysed for stereological studies spermatogonia) indices (Oghbaei et al, 2018) were calculated in each animal as previously described.…”
Section: Histological and Stereological Analysis Of Testismentioning
confidence: 99%
“…On this basis, we followed the previous protocol that lasts over a period of 32 ± 1 days 20 . Rats received 1 mg OVA (Sigma‐Aldrich) via an intraperitoneal route on days 1 and 8.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, cells were re‐suspended in low‐content glucose Dulbecco's modified Eagle's medium (DMEM/LG; Biosera) containing 10% FBS and 1% Pen‐Strep solution (Biosera). Cells were sub‐cultured after reaching 70% to 80% confluence 20 . Passages 3 to 6 were used in the current experiment.…”
Section: Methodsmentioning
confidence: 99%